Comparative Study of Blockchain and Traditional Database Systems for Secure Transactions in Nigeria - Olumide, Ayotunde (International Journal of Computing and Engineering, 2024)
Purpose: The purpose of this article was to analyze comparative study of blockchain and traditional database systems for secure transactions in Nigeria. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: A comparative study of blockchain and traditional databases for secure transactions in Nigeria and Japan reveals that blockchain offers superior security due to its decentralization and cryptography, while traditional databases are more efficient and cost-effective. Japan has embraced blockchain faster, particularly in finance and supply chains, due to its advanced infrastructure and clearer regulations. In contrast, Nigeria is slowly adopting blockchain, focusing on financial inclusion and digital security. Unique Contribution to Theory, Practice and Policy: Technology acceptance model (TAM), diffusion of innovations (DOI) theory, systems theory may be used to anchor future studies on the comparative study of blockchain and traditional database systems for secure transactions in Nigeria. From a practical standpoint, organizations should consider adopting hybrid solutions that leverage the strengths of both blockchain and traditional database systems. On the policy front, governments and regulatory bodies must play a crucial role in creating standardized guidelines and regulations for the adoption of blockchain and traditional database systems.